An experimental and observational study of interspecific territoriality between the blackcap Sylvia atricapilla (Linnaeus) and the garden warbler Sylvia borin (Boddaert) - Garcia, E; Garcia, Ernest Francis (1981)
﻿ Ecological divergence between Blackcaps and Garden Warblers appears to be incomplete. They resemble each other closely in morphology and their foraging behaviour and food (in the breeding season) are at least broadly similar. Nevertheless, they are sympatric and occur together in a wide range of habitats although Garden Warblers are proportionately commoner in lower, denser vegetation. The two species are strongly interspecifically territorial where they occur together. However, Blackcaps are more interspecifically aggressive than Garden Warblers and are clearly dominant to them in interactions. Blackcaps respond just as strongly to playback of Garden Warbler song as they do to that of Blackcap song. They sometimes intrude into Garden Warbler territories and seek- out and chase the territory holders. In contrast, with rare exceptions, any Garden Warblers which intrude into Blackcap territories are attacked and chased until they leave the area. Also, during song playback experiments, Garden Warblers approach the loudspeaker less closely in response to Blackcap song than they do to Garden Warbler song. Many Blackcaps arrive on the breeding grounds before the earliest Garden Warblers do. A removal experiment, in which such established Blackcaps were systematically removed, showed that some of them had been keeping-out potential Garden Warbler settlers, since the latter then readily established territories and bred in a large part of the Blackcap-free zone. Normally, Garden Warblers have their territories outside Blackcat>-occupied habitat, partly because they are prevented by the aggressiveness of the Blackcaps from settling elsewhere. However, observation and song playback experiments have shown that, once established, Garden Warblers do defend their territories against both conspecifics and Blackcaps. Blackcaps have recently increased dramatically in Britain and Garden Warblers have decreased simultaneously. However, although Blackcaps can limit the local breeding densities of Garden Warblers in any one year, it is not yet clear whether Blackcap numbers are a significant factor in determining the total sizes of Garden Warbler populations.